Project Stakeholder Analysis in Temadore Bridge Construction Development - Rafsanjani, Hud; Rarasati, Ayomi Dita (UI Scholars Hub, 2024)
The construction of bridge is important due to its ability to link communities through land-road connection, thereby saving time and increasing productivity of those living in these areas. Therefore, this research evaluated the Temadore bridge, built to link Ternate City, Maitara land and Tidore City by road to enhance movement and reduce disparities in assessing both areas. Data were collected using the Interpretative Structural Modeling (ISM) which searched for and identified several variables according to the dependence power and driving power. The result showed that construction of bridge increased the movement of community activities and productivity, thereby leading to growth.